Teacher Recruitment, Motivation and Retention at Rural Schools in Namibia - Elock Emvula Shikalepo (Foxton Books, 2019)
Teacher motivation is an integral part of the success of the teaching and learning processes. The purpose of this study was to establish the factors underlying teacher recruitment, motivation and retention within a rural context. A case study design was employed as a methodology for the study. The collected data was analysed by establishing themes and emerging categories. The study established that teachers at rural schools were motivated by crucial work-related factors which were both intrinsic and extrinsic in nature. Employment opportunities, family background, leadership, rural environment and support services were some of the major factors motivating teacher to be recruited and retained with rural school teaching. The study recommended that school leaders should acquire a holistic understanding of the diverse factors motivating teachers, so that they can nurture these factors and motivate teachers appropriately. This will ensure that rural schools remains with motivated teaching personnel for improved performance.